Numerical study of starch-gluten dough: deformation and extrusion - Mohammed, M. A. P.; Baharuddin, A. S.; Wakisaka, M. (Elsevier, 2022)
Numerical investigation of starch-gluten model was conducted using composite micromechanics approach, which considered starch as circular filler embedded/surrounded by gluten matrix. The model developed was then compared with different starch-gluten models reported in literatures. The starch-gluten circular filler model simulations with different starch-filler diameters showed consistent results with the dough microstructure model, which suggested that the model can be used for dough process simulation, such as extrusion-based printing. Using similar approach, the extrusion model was then developed using billet representing starch-gluten dough being forced through the barrel with dies at different entry angles and ram extrusion speeds. Reducing the entry angles increased the extrusion force due to viscoelastic behaviour of dough. Likewise, a similar increased force results were obtained when the extrusion speeds were increased.